INDIVIDUAL TASKS AS A MEANS FORMATION OF FUTURE CAPACITIES OF THE FUTURE TEACHERS OF MATHEMATICS - Ivanova, V.V. (Pedagogy of Higher and Secondary Education, 2008)
The individual tasks as a method of forming creative abilities of future mathematics teachers are being considenred in the article.